Analysis of thin sections from ash deposits within the cairn (Scottish Historical and Archaeological Internet Reports, 2005)
The analysis of the thin-section evidence offers some guidance to the archaeological interpretation of these deposits. The soil underlying the sediments had been truncated shortly before their deposition; this activity may have been part of the preparation of the site for the cist and cairn. The sediments can be divided into two types: cold fuel ash from the fires burning peaty turves and unidentified herbaceous plants. The role of the layers of plants in any burial activity is obscure but they have been repeatedly interleaved with ash and this suggests more than an accidental presence in the deposits.